نزع الملكية من اجل المنفعة العمومية في التشريع الجزائري - بلوافــــي, الوافــــي (My University, 2023)
يعتبر اجراء نزع الملكية من اجل المنفعة العمومية امتيازا للإدارة في مواجهة الفرد تستعمله في إطار تمارسهالادارة باعتباره وجها لامتياز السلطة العامة في مواجهة الفرد الذي امتنع على التسليم للإدارة بالملكية او حق عيني عقاري في إطار التفاوض معها على التنازل على هذا الحق بالطرقالودية،وتمارس الادارة حق الامتياز من اجل تحقيق منفعة عامة فقط. ولكون الاجراء فيه مساس بحق من حقوق الافراد الدستورية فقد خصه المشرع الجزائري بقانون خاص، والحقه بمراسيم تنفيذية، لضمان حسن التطبيق والتنفيذ. وقد واكب المشرع تطورات المجتمع ومتطلباته، من خلال التصدي لبعض النقائص في كل مرة بموجب احكام لاحقة لقانون نزع الملكية من اجل المنفعة العمومية، الا ان الحاجة تبقى دائما لتحديثات اخرى تخص تطبيق مختلف احكام هذا القانون.It isconsidered a foreignmeasure in exchange for ownership, and generalprivilegeis a privilege and a privilege in the face of the individual, whichyou use in the context of sex and as a face to the public authority’sprivileges in the face of the individualwhorefrainedfromgivingthis right in amicableways. The administration exercises the franchise for the purpose of achieving public interestonly And because the procedureviolates the right of the rights of original copies, the Algerian legislator has singled out a speciallaw for him, and his right to beexecuted by executivedecrees, good execution and implementation. The legislator has kept pace with the development of society and itsrequirements, throughsome inscriptions in the property tables for the public benefit, but the needalwaysremains for other updates related to the application of the various provisions of thislaw.
مذكرة ماستر
Keywords: : نزع الملكية – المنفعة العمومية; Expropriation – Public Benefit